Ca2+/TEMPO dual-modified bacterial nanocellulose interfaces for programmable Pickering emulsions and controlled curcumin release - Nan Zhang; Xueyan Gao; Yu Zhang; Yonghao Li; Xuan Hu; Lingfei Li; Wei Liu (Food Hydrocolloids, 2026)

A self-powered intelligent wireless electronic mouse with user identity recognition based on multi-source energy harvesting - Jinyan Feng; Yiyan Zhang; Kai Zhang; Can Hu; Jiatian Song; Qile Yu; Guanping Wang; Lingfei Qi (Chemical Engineering Journal, 2026)

W1/O/W2 double emulsions stabilized by natural diosgenin and ultrasound-treated pea protein nanoparticles: A plant-based system for iron fortification - Chao Zhang; Xuan Hu; Yu Zhang; Lingfei Li; Shufang Zhao; Quanfang Zhang; Yanli Yu; Wei Liu (Food Hydrocolloids, 2026)

Numerical Investigation of Flow Field Characteristics Around a Monopile Foundation with Collar Protection - Lei Wu; Hao Meng; Haifei Sun; Lingfei Yu; Dake Chen; Xiyu Zhao; Dawei Guan (Journal of Marine Science and Engineering, 2025)
Collar structures are widely used to protect monopile foundations from scour, but their geometric obstruction hinders direct observation of the surrounding flow in physical experiments. To overcome this limitation, this study employs large-eddy simulation (LES) to investigate the flow characteristics around a monopile with collar protection. The LES model was validated against well-documented experimental data of pile-induced flow, confirming its reliability. Simulations under flat-bed and equilibrium scour conditions were conducted to evaluate the effects of the collar on time-averaged velocity, vortex dynamics, and turbulence intensity. The results show that the collar substantially weakens the upstream accelerated flow, suppresses horseshoe vortex formation, and reduces both the strength and extent of sidewall currents. Under flatbed conditions, the side-flow intensity decreases by 24.3% and the accelerated flow area is reduced by 93.3%. A counter-rotating vortex beneath the collar dissipates kinetic energy and simplifies the near-bed vortex system, thereby mitigating scour. However, the protective effect diminishes with increasing inflow velocity, with turbulence intensity rising by 159% for a 14% velocity increase. Overall, this study provides deeper insights into the protective mechanisms of collar structures, advancing the understanding of their effectiveness and limitations in monopile scour protection.

Deciphering the microbial mechanisms underlying glucose induced soil priming effects under low and high nutrient levels - Jiaqi Wang; Xichang Zhang; Yingyi Fu; Lukas Van Zwieten; Han Sun; Georg Guggenberger; Lingfei Hu; Yu Luo; Tida Ge; Yakov Kuzyakov (European Journal of Soil Biology, 2025)

Relationship between internal metal exposure and thyroid cancer incidence: a case-control study simultaneously validated by BKMR and WQS models - Muke Yu; Jingyu Xun; Yiming Ge; Xinjie Li; Xulong Chen; Lingfei Cui; Xidi Wang; Mingxia Zhang; Zhaomin Xing; Liang Deng; NiJiati AiErken; Shaoyou Lu; et al. (Food and Chemical Toxicology, 2025)

Inhibitory activity of Moringa oleifera seed oil nanoemulsion against Staphylococcus aureus and its application in chicken meat preservation - Shuyun Ma; Lingfei Li; Ju Qu; Yu Yang; Qiu Yang; Yang Tian (Food Bioscience, 2025)

Calcium self-release bioremediation system combined with microbially induced calcium precipitation for the removal of ammonium nitrogen, phosphorus and heavy metals - Lingfei Zhang; Junfeng Su; Shuyu Liu; Tinglin Huang; Zhao Wang; Yu Liu; Chenxi Hou; Xinjie Wang (Journal of Environmental Chemical Engineering, 2024)

Advanced orthogonal analysis of multi-factorial interactions influencing co-combustion performance and pollution reduction potential of coal gangue and biomass in oxy-fuel combustion conditions - Qingxiang Wang; Lingfei Liu; Maiwei Chen; Zijian Yu; Jiaxu Tang; Yaojie Tu (Process Safety and Environmental Protection, 2024)

Grazing exclusion jeopardizes plant biodiversity effect but enhances dryness effect on multifunctionality in arid grasslands - Lingfei Yu; Wenjuan Sun; Haiyang Zhang; Nan Cong; Yuan Chen; Jinjiao Hu; Xin Jing (Agriculture, Ecosystems & Environment, 2024)

Do rice growth and yield respond similarly to abrupt and gradual increase in atmospheric CO2? - Kai Yang; Yao Huang; Jingrui Yang; Chunhua Lv; Wenjuan Sun; Zhenghua Hu; Chunyan You; Lingfei Yu (Science of The Total Environment, 2024)

Failure process and mechanism analysis of rock slope induced by underground mining: a case study in Yanqianshan open-pit mine, China - Lingfei Zhang; Zhonghui Chen; Zihan Zhou; Jianshuai Hao; Yu Zhou; Yanjun Shen (Bulletin of Engineering Geology and the Environment, 2023)

Heavy metal contamination collapses trophic interactions in the soil microbial food web via bottom-up regulation - Xuehua Wang; Zhongmin Dai; Jiahui Lin; Haochun Zhao; Haodan Yu; Bin Ma; Lingfei Hu; Jiachun Shi; Xiaoyun Chen; Manqiang Liu; Xin Ke; Yijun Yu; et al. (Soil Biology and Biochemistry, 2023)

Biocrystal-encased manganese ferrite coupling with peroxydisulfate: Synergistic mechanism of adsorption and catalysis towards tetracycline removal - Zhao Wang; Junfeng Su; Tinglin Huang; Yu Liu; Tingbao Zhao; Jiawei Li; Lingfei Zhang (Chemical Engineering Journal, 2023)

Removal of carbonaceous and nitrogenous disinfection by-product precursors in biological activated carbon process of drinking water: Is service life a pivotal factor? - Yan Wang; Lingfei Li; Huiyu Dong; Qi Wang; Shuang Liu; Minhui Wu; Jianwei Yu; Zhimin Qiang (Chemical Engineering Journal, 2023)

Hydrogen-bond induced enhanced emission ratiometric fluorescent handy needle for visualization assay of amoxicillin by smartphone sensing platform - Lingfei Li; Liang Yang; Dan Lin; Shihao Xu; Chunsheng Mei; Shaoming Yu; Changlong Jiang (Journal of Hazardous Materials, 2023)

The determiner of photosynthetic acclimation induced by biochemical limitation under elevated CO2 in japonica rice - Kai Yang; Yao Huang; Jingrui Yang; Lingfei Yu; Zhenghua Hu; Wenjuan Sun; Qing Zhang (Journal of Plant Physiology, 2023)

Metformin Hydrochloride Mucosal Nanoparticles-Based Enteric Capsule for Prolonged Intestinal Residence Time, Improved Bioavailability, and Hypoglycemic Effect - Wenjie Lu; Lingfei Yu; Lujun Wang; Songlin Liu; Manman Li; Zijun Wu; Shengqi Chen; Rongfeng Hu; Haiping Hao (AAPS PharmSciTech, 2022)

Carbon sequestration in soil and biomass under native and non-native mangrove ecosystems - Ziming Zhang; Ying Wang; Yakun Zhu; Kehong He; Tingting Li; Umakant Mishra; Yisheng Peng; Fan Wang; Lingfei Yu; Xiaosong Zhao; Liye Zhu; Xudong Zhu; et al. (Plant and Soil, 2022)

Terrestrial carbon sinks in China and around the world and their contribution to carbon neutrality - Yuanhe Yang; Yue Shi; Wenjuan Sun; Jinfeng Chang; Jianxiao Zhu; Leiyi Chen; Xin Wang; Yanpei Guo; Hongtu Zhang; Lingfei Yu; Shuqing Zhao; Kang Xu; et al. (Science China Life Sciences, 2022)

Hyperspectral characteristics and inversion model estimation of winter wheat under different elevated CO 2 concentrations - Chao Liu; Zhenghua Hu; A.R.M. Towfiqul Islam; Rui Kong; Lingfei Yu; Yuanyuan Wang; Shutao Chen; Xuesong Zhang (International Journal of Remote Sensing, 2021)

Climate drives global soil carbon sequestration and crop yield changes under conservation agriculture - Wenjuan Sun; Josep G. Canadell; Lijun Yu; Lingfei Yu; Wen Zhang; Pete Smith; Tony Fischer; Yao Huang (Global Change Biology, 2020)
Conservation agriculture has been shown to have multiple benefits for soils, crop yield and the environment, and consequently, no‐till, the central practice of conservation agriculture, has rapidly expanded. However, studies show that the potential for carbon (C) sequestration in no‐till farming sometimes is not realized, let alone the ability to maintain or improve crop yield. Here we present a global analysis of no‐till‐induced changes of soil C and crop yield based on 260 and 1,970 paired studies; respectively. We show that, relative to local conventional tillage, arid regions can benefit the most from conservation agriculture by achieving a win‐win outcome of enhanced C sequestration and increased crop yield. However, more humid regions are more likely to increase SOC only, while some colder regions have yield losses and soil C loss as likely as soil C gains. In addition to site‐specific characteristics and management, a careful assessment of the regional climate is needed to determine the potential benefits of adopting conservation agriculture.

Molecular mechanisms of water table lowering and nitrogen deposition in affecting greenhouse gas emissions from a Tibetan alpine wetland - Hao Wang; Lingfei Yu; Zhenhua Zhang; Wei Liu; Litong Chen; Guangmin Cao; Haowei Yue; Jizhong Zhou; Yunfeng Yang; Yanhong Tang; Jin‐Sheng He (Global Change Biology, 2017)
Rapid climate change and intensified human activities have resulted in water table lowering ( WTL ) and enhanced nitrogen (N) deposition in Tibetan alpine wetlands. These changes may alter the magnitude and direction of greenhouse gas ( GHG ) emissions, affecting the climate impact of these fragile ecosystems. We conducted a mesocosm experiment combined with a metagenomics approach (GeoChip 5.0) to elucidate the effects of WTL (−20 cm relative to control) and N deposition (30 kg N ha −1 yr −1 ) on carbon dioxide ( CO 2 ), methane ( CH 4 ) and nitrous oxide (N 2 O) fluxes as well as the underlying mechanisms. Our results showed that WTL reduced CH 4 emissions by 57.4% averaged over three growing seasons compared with no‐ WTL plots, but had no significant effect on net CO 2 uptake or N 2 O flux. N deposition increased net CO 2 uptake by 25.2% in comparison with no‐N deposition plots and turned the mesocosms from N 2 O sinks to N 2 O sources, but had little influence on CH 4 emissions. The interactions between WTL and N deposition were not detected in all GHG emissions. As a result, WTL and N deposition both reduced the global warming potential ( GWP ) of growing season GHG budgets on a 100‐year time horizon, but via different mechanisms. WTL reduced GWP from 337.3 to −480.1 g CO 2 ‐eq m −2 mostly because of decreased CH 4 emissions, while N deposition reduced GWP from 21.0 to −163.8 g CO 2 ‐eq m −2 , mainly owing to increased net CO 2 uptake. GeoChip analysis revealed that decreased CH 4 production potential, rather than increased CH 4 oxidation potential, may lead to the reduction in net CH 4 emissions, and decreased nitrification potential and increased denitrification potential affected N 2 O fluxes under WTL conditions. Our study highlights the importance of microbial mechanisms in regulating ecosystem‐scale GHG responses to environmental changes.

Therapeutic effects of histone deacetylase inhibitors in a murine asthma model - Yuan Ren; Xinming Su; Lingfei Kong; Menglu Li; Xuan Zhao; Na Yu; Jian Kang (Inflammation Research, 2016)

Assessment the protection performance of different level personal respiratory protection masks against viral aerosol - ZhanBo Wen; Long Yu; WenHui Yang; LingFei Hu; Na Li; Jie Wang; JinSong Li; JianChun Lu; XiaoKai Dong; Zhe Yin; Ke Zhang (Aerobiologia, 2013)